RELATIONSHIPS BETWEEN RENAL VASCULATURE ABNORMALITIES AND ARTERIAL HYPERTENSION IN CHILDREN AND ADOLESCENTS. (June 2018) - Giordano, U.; Yammine, M.L.; Chinali, M.; Secinaro, A.; Turchetta, A.; Cafiero, G.; Matteucci, M.C.
Abstract : Objective: This study investigated hypertensive children for non-stenotic renal vascular abnormalities, in terms of number of arteries, size, shape, course and possible relationships with arterial hypertension Design and method: Patients referred for elevated blood pressure were considered and those with known causes for secondary hypertension were excluded from the study. Seventy-two patients were selected with persistent hypertension (blood pressure > 95th centile) of more than one year's duration and confirmed by 24 h ambulatory blood pressure monitoring. All patients underwent abdominal CT-angiography or MRI scanning to rule out possible renal artery stenosis and echocardiography to evaluate left ventricular diastoli dysfunction and/or left ventricular hypertrophy. Antihypertensive treatment with Candesartan was used to control blood pressure. Results: Most of patients (59/72 – 82%) had abnormal renal vasculature, either arterial or venous, in terms of the number of arteries, size, shape and course. 48/59 pts (81%) had a polar accessory artery which was unilateral in 39 (81%) patients and in 9 (19%) was bilateral. Five of 59 patients (8%) showed a so-called "nut-cracker syndrome" (2 of whom had also triple left renal veins). Only 13/72 patients (18%) showed a normal renal vasculature pattern. Thirty patients (40%) showed left ventricular diastolic dysfunction/hypertrophy. All patients were well controlled with Candesartan and no patients had any drug side-effects. Creatinine and potassium remained always in the normal range during treatment Conclusions: The incidence of hypertension in children is increasing in recent decades for several reasons, particularly obesity. Young patients with persistent elevated blood pressure also should be investigated for renal vasculature abnormalities and possible left ventricular diastolic dysfunction/hypertrophy which may be treatable with Candesartan. The Poiseuille equation suggests that both the radius and the length of the vessel may be operative in patients with abnormal renal arteries.